New use of psychotropic medication after hospitalization among people with dementia - Möllers, Tobias; Perna, Laura; Stocker, Hannah; Ihle, Peter; Schubert, Ingrid; Schöttker, Ben; Frölich, Lutz; Brenner, Hermann (International journal of geriatric psychiatry, 2020)
Objectives Psychotropic medication is commonly used among people with dementia (PWD), but it shows modest efficacy and it has been associated with severe adverse events. Hospitalizations are an opportunity for medication management as well as treatment recommendations for outpatient physicians. The aim of this study was to asses factors associated with new use of psychotropic medication after hospitalization among PWD. Methods We conducted a retrospective dynamic cohort study from 2004 to 2015 using claims data from a German health insurance company. PWD were identified by an algorithm that included ICD-10 diagnosis and diagnostic measures. The medication classes included were antidepressants, antipsychotics, anxiolytics or hypnotics/sedatives, and Alzheimer's medication. The assessment period was up to 30 days after discharge from the hospital across four hospitalizations. Results The main predictors for new use of psychotropic medication were similar across medication classes. Neuropsychiatric symptoms (NPS) and the need of care were associated with higher odds of new use of antidepressants, antipsychotics, and anxiolytics or hypnotics/sedatives. A hospital stay due to dementia was an independent predictor for new use across medication classes as well. Delirium increased the odds for new use of antipsychotics and anxiolytics or hypnotics/sedatives. Conclusions Factors associated with new use of psychotropic medication included delirium, NPS, and the need of care in PWD. The findings highlight the need for preventive interventions and non-medical treatment options in regards to delirium and NPS as well as for a more intensive use of screening tools for inappropriate medication use among PWD. Key points The percentage of new users was 1.8%, 7.1%, 2.1%, and 2.5% across hospitalizations for antidepressants, antipsychotics, anxiolytics or hypnotics/sedatives, and Alzheimer's medication, respectively. 83.0%, 61.9%, 56.9%, and 88.1% of new users received antidepressants, antipsychotics, anxiolytics or hypnotics/sedatives, and Alzheimer's medication for more than 6 weeks. Delirium and neuropsychiatric symptoms were associated with significantly increased odds of new psychotropic medication use. Hospital stays due to dementia and the need of care were predictors for new use of psychotropic medication.
Gesehen am 10.06.2020